Collaborative Production in the Creative Industries - Gandini, Alessandro; Graham, James (University of Westminster Press, 2017)
"In recent years research into creative labour and cultural work has usually addressed the politics of production in these fields, but the sociotechnical and aesthetic dimensions of collaborative creative work have been somewhat overlooked. This book aims to address this gap. Through case studies that range from TV showrunning to independent publishing, from the film industry to social media platforms such as Tumblr and Wattpad, this collection develops a critical understanding of the integral role collaboration plays in contemporary media and culture. It draws attention to diverse kinds of creative collaboration afforded via the intermediation of digital platforms and networked publics. It considers how these are incorporated into emergent market paradigms and investigates the complicated forms of subjectivity that develop as a consequence. But it also acknowledges historical continuities, not least in terms of the continued exploitation of 'support personnel' and of resulting artistic conflicts but also of alternative models that resist the precarious nature of contemporary cultural work. Finally, this volume attempts to situate creative collaboration in broader social and economic contexts, where the experience and outcomes of such work have proved more problematic than the rich potential of their promise would lead us to expect. "